Designing the world's best children's hospitals 3 the future of healing environments - Komiske, Bruce King (Images Pub., 2012)
Following the success of 'Designing the World's Best Children's Hospitals' 1 and 2, this new publication provides an up-to-date reference guide for healthcare teams, design professionals and community members, who together engage in the exciting process of creating new healing environments for children's hospitals or paediatric units.